2017
DOI: 10.4236/cn.2017.91003
|View full text |Cite
|
Sign up to set email alerts
|

Operation Research Based Techniques in Wireless Sensors Networks

Abstract: In recent years, we have seen an increasing interest in developing and designing Wireless Sensor Networks (WSNs). WSNs consist of large number of nodes, with wireless communications and computation abilities that can be used in variety of domains. It has been used in areas that have direct contact with monitoring and gathering data, to name few, health monitoring, military surveillance, geological monitoring (Earthquakes, Volcanoes, Tsunami), agriculture control and many more. However, the design and implement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…These questions give rise to new complex problems and challenges in Operations Research. Indeed, Operation Research is widely used to solve WSNs optimization problems; such as improving network performance and maximizing the lifetime of the system [43,26].…”
Section: Energy Optimization In Multi-hop Wsnsmentioning
confidence: 99%
“…These questions give rise to new complex problems and challenges in Operations Research. Indeed, Operation Research is widely used to solve WSNs optimization problems; such as improving network performance and maximizing the lifetime of the system [43,26].…”
Section: Energy Optimization In Multi-hop Wsnsmentioning
confidence: 99%
“…The routing algorithm is used to determine mathematically the best path to take. In (Dilo et al, 2011) (Mahlous & Tounsi, 2017) the authors showed that the use of shortest path tree in routing is the most common technique used for routing within WSNs. Hence, they exhibited the issues with shortest path tree, which is the unbalanced load between the sensors and the disparity in the energy used by such nodes.…”
Section: Related Workmentioning
confidence: 99%
“…All sensors can route data or collect it from their environment. There are several real-life applications for WSNs, such as fire detection, military surveillance, monitoring, and physiological monitoring of patient, wild fires surveillance, grid monitoring, water distribution monitoring and much more (Jing, 2017;Mahlous & Tounsi, 2017;Le Nguyen et al, 2019;Sharma & Ghose, 2010;Thakkar & Kotecha, 2014). Due to their limited capacity, one of the main challenges to WSNs is how to increase the network lifetime by performing data routing that consume less energy.…”
Section: Introductionmentioning
confidence: 99%